The Impact of Religious Leadership on Islamic Education Development - Nasution, Puli Taslim; Nur, Kholidah (Universitas KH. Abdul Chalim Pacet Mojokerto, 2025)
This study explores the role of religious leaders in promoting Islamic education and fostering community harmony, particularly in communities where social norms and religious values are not widely upheld. As moral role models and spiritual guides, religious leaders are crucial in addressing behavioural issues and raising religious awareness within society. The research uses a quantitative approach, with simple linear regression analysis using SPSS software to examine the relationship between religious leadership and the development of Islamic education. The analysis reveals that 64.9% of the variance in the development of Islamic education can be attributed to the influence of religious leaders, while other factors influence the remaining 35.1%. These findings indicate that religious leaders can significantly impact educational outcomes through guidance and active community engagement. However, the study also highlights the need for better strategies to increase public enthusiasm for religious activities, particularly in communities that are less aware of or do not practice proper religious behaviour